ANALISA UJI TEKAN, KERAPATAN DENSITAS DAN MIKROSTRUKTUR TERHADAP KOMPOSIT BAHAN BAKU TEAKWOOD SERBUK GERGAJI KAYU - Nurkholis Islamuddin; Wisma Soedarmadji (Prodi Teknik Mesin Universitas Yudharta, 2020)
There are two problems in this research, the quantity of density and microstruckture of the composite raw material of teakwood from sawdust. So this research is for knowing the quantity of density and microstruckture of the composite raw material of teakwood from sawdust. This research is using quantitative method. The result of this research is quantity of density of the composite raw material of teakwood from sawdust is 5 grams of the teakwood sawdust has more density than another dust. For the microstruckture test said that the value of G, the sawdust mean every 5 grams is 60 mm, so more sawdust weight the density more high. The researcher suggest that next research should add another composition so that it can create more high structure and analize the structure Microskopic for knowing the content of the structure more intensive.